An insight into variability and association among yield and its components under alkalinity and inland salinity stress in rice (Oryza sativa L.) - Gaddam, Shiva Prasad; Katragadda, Sumalini; Nelagundarashi, Lingaiah; Vindla, Sridhar (ORYZA-An International Journal of Rice, 2024)
An experiment was conducted to study the variability, correlation, direct and indirect effects of yield and itsattributing traits in 36 genotypes and to identify suitable parents for breeding of alkalinity and inland salinitystress tolerant lines at ARS, Kampasagar, Nalgonda during rabi, 2021-22. Analysis of variance revealed plenteousquantum of variation among the tested genotypes. Wide variation, high PCV, GCV, heritability and geneticadvance were observed for seedling mortality, sterility percentage and number of filled grains per panicle.Number of productive tillers/hill and number of filled grains per panicle had a positive and significant correlationwith yield whereas seedling mortality and sterility percentage had a negative and significant association withyield. Path analysis inferred that traits such as number of productive tillers/hill, number of grains per panicleand 1000 grain weight had a positive direct effect on yield. Hence,priority should be given to the abovementioned traits to develop alkalinity and inland saline tolerant rice cultivars. Lines CT118911, Sahel177,M202, and KPS10654 were found promising to be utilized as tolerant parents in the breeding programmes.